2009
DOI: 10.1128/iai.00310-09
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-Dioxygenase Is Involved in Defense againstNeospora caninumin Human and Bovine Cells

Abstract: Neospora caninum is an apicomplexan parasite closely related to Toxoplasma gondii. In nature this parasite is found especially in dogs and cattle, but it may also infect other livestock. The growth of N. caninum, which is an obligate intracellular parasite, is controlled mainly by the cell-mediated immune response. During infection the cytokine gamma interferon (IFN-␥) plays a prominent role in regulating the growth of N. caninum in natural and experimental disease. The present study showed that induction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In cattle, little work has been performed to evaluate the role of IDO in both normal and pathologic states. While studies would suggest that IDO plays a role in protection against intracellular pathogens such as N. caninum, other studies have found that IDO may allow persistence of M. avium subsp paratuberculosis within mononuclear cells of both cattle and sheep (Plain et al, 2011;Spekker et al, 2009). In addition, IDO may have a role in recognition of pregnancy and promoting tolerance to the fetal allograft (Groebner et al, 2011).…”
Section: Groupmentioning
confidence: 97%
See 1 more Smart Citation
“…In cattle, little work has been performed to evaluate the role of IDO in both normal and pathologic states. While studies would suggest that IDO plays a role in protection against intracellular pathogens such as N. caninum, other studies have found that IDO may allow persistence of M. avium subsp paratuberculosis within mononuclear cells of both cattle and sheep (Plain et al, 2011;Spekker et al, 2009). In addition, IDO may have a role in recognition of pregnancy and promoting tolerance to the fetal allograft (Groebner et al, 2011).…”
Section: Groupmentioning
confidence: 97%
“…Little research has been performed to evaluate the role of IDO in diseases of cattle. It has been shown that IDO is required for in vitro inhibition of Neospora caninum in bovine fibroblasts and endothelial cells (Spekker et al, 2009). In addition, one study demonstrated that IDO expression and activity are increased in the endometrium of cattle 18 days pregnant when compared to non-pregnant controls (Groebner et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Various in vitro studies have shown that the anti-parasitic actions of certain cytokines relate to their ability to induce IDO1. For example, IFNγ and TNFα have been reported to inhibit Neospora caninum (a parasite causing abortion in livestock) in human cell lines, primary cells and bovine fibroblast-like cells [492,493], Encephalitozoon intestinalis (an opportunistic diarrhoeal parasite associated with AIDS) in mouse enterocyte cells and human epithelial colorectal adenocarcinoma cells [494], Leishmania donovani (an intracellular protozoan that causes leishmaniasis) in human macrophages [441], as well as the growth of T. gondii (which can cause severe toxoplasmosis, particularly in the immunocompromised) in primary human cells and human cell lines, primarily via IDO1-mediated L-Trp starvation [441,471,[495][496][497][498][499][500]. The effectiveness of IFNγ -induced IDO1 at inhibiting T. gondii infection in vitro is, however, impaired in cells cultured under low O 2 tension [124], i.e.…”
Section: Parasitesmentioning
confidence: 99%
“…Local accumulation of kynurenine metabolites, in particular, quinolinic acid, following IDO induction may represent a potentially detrimental event because quinolinic acid is a potent excitotoxin, and its overproduction has been linked to neuronal damage occurring in brain inflammation [672], initiation of lipid peroxidation [673], and development of disturbances in gluconeogenesis in the liver [674]. Spekker et al [675] proposed that IDO is responsible for the suppression of Neospora caninum growth, and other studies on T. gondii suggested that its growth could be contained when certain immune cells including dendritic cells were actively expressing IDO [163]. Moreover, L-tryptophan-L-kynurenine pathway metabolism accelerated by T. gondii infection was found to be abolished in IFN-γ-gene-deficient mice, and an antitoxoplasmatic mechanism of cross-regulation between iNOS and IDO that may vary among tissues, was demonstrated [671] (Figure 1).…”
Section: T Gondii Infectionmentioning
confidence: 99%